2010
DOI: 10.4064/fm209-3-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hausdorff dimension of the projections of self-affine carpets

Abstract: Abstract. We study the orthogonal projections of a large class of self-affine carpets, which contains the carpets of Bedford and McMullen as special cases. Our main result is that if Λ is such a carpet, and certain natural irrationality conditions hold, then every orthogonal projection of Λ in a non-principal direction has Hausdorff dimension min(γ, 1), where γ is the Hausdorff dimension of Λ. This generalizes a recent result of Peres and Shmerkin on sums of Cantor sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…It suffices to prove that for any ε > 0 we can find a subset of F which has lower dimension within ε of the Hausdorff dimension. Via an elegant application of Stirling's formula, Ferguson-Jordan-Shmerkin [FJS,Lemma 4.3] showed that one can always find a subset of such a carpet generated by a subsystem of an iterate of the original IFS which both has Hausdorff dimension within ε of the original Hausdorff dimension and has the key additional property that the fibres are uniform. Then it follows from [Fr,Theorem 2.13] that the lower dimension and the Hausdorff dimension of the subset coincide, thus proving the result.…”
Section: Self-affine Carpetsmentioning
confidence: 99%
“…It suffices to prove that for any ε > 0 we can find a subset of F which has lower dimension within ε of the Hausdorff dimension. Via an elegant application of Stirling's formula, Ferguson-Jordan-Shmerkin [FJS,Lemma 4.3] showed that one can always find a subset of such a carpet generated by a subsystem of an iterate of the original IFS which both has Hausdorff dimension within ε of the original Hausdorff dimension and has the key additional property that the fibres are uniform. Then it follows from [Fr,Theorem 2.13] that the lower dimension and the Hausdorff dimension of the subset coincide, thus proving the result.…”
Section: Self-affine Carpetsmentioning
confidence: 99%
“…Proof. Let Γ be the set constructed by Proposition 4.3 with ε/2 in place of ε, and with n chosen large enough that e −nε/2 < 1 16 . We will find an integer n > n and a set Γ ⊆ {1, .…”
Section: Regular Subsystemsmentioning
confidence: 99%
“…Early results of this type for sets were obtained in [3,21,11]. Recall that the (lower) Hausdorff dimension of a measure µ is…”
Section: Introductionmentioning
confidence: 99%